Islamic Legal Politics in Post-Reformation Indonesia: Sharia Legislation, Decentralization, and Democratic Dynamics - Muhammad Hizbullah; Haidir Haidir; Yeny Nasril (Hukum Keluarga Islam IAIN LANGSA, 2025)
The 1998 Reformism expanded democratic and decentralized spaces, yet scholarly engagement with sharia legislation often remains confined to normative or formal frameworks, leaving its intersections with electoral competition, identity politics, and shifting power configurations insufficiently examined. This study explores the development of Islamic legal politics in post-reform Indonesia, with particular attention to the dynamics of sharia legislation within a constitutional democracy. Employing a normative legal approach enriched by historical and conceptual perspectives, it analyzes secondary legal materials to assess implications for democracy, constitutionalism, and human rights. Findings reveal that post-reform sharia legislation is shaped by complex interactions among political elites’ electoral strategies, the mobilization of religious identity, and decentralized structures that facilitate symbolic regulation at the local level. While national laws on waqf, zakat, and sharia banking address substantive socio-economic needs, local morality regulations—such as dress codes or alcohol restrictions—frequently serve symbolic and populist functions. This study contributes a contextual and integrative framework for understanding Islamic legal politics, underscoring the importance of inclusive paradigms attentive to social plurality, constitutional principles, and gender justice in Indonesia’s multicultural society.